Developing 8D Building Information Modeling and Virtual Reality to Minimize Safety Hazards In Construction Building Projects - Jati Utomo Dwi Hatmoko; Fajar Mega Rakhma; Naufal Sultan Azzam Khan; Frida Kristiani (Diponegoro University, 2025)
Construction accidents remain a significant challenge in the construction industry. One of the biggest challenges is to design and communicate the safety plan of the project to all parties and people working on the construction site. The emergence of 8D Building Information Modeling (BIM) represents a technological advancement focusing on project safety, yet its implementation remains limited globally, including in Indonesia. This research was aimed to develop an 8D BIM model of a building project which allow project stakeholders to plan and examine the safety aspect of the project via virtual reality (VR). The digital model allows stakeholders to virtually identify construction hazards, plan the placement of safety equipment, and simulate safety protocols before implementation. It also facilitates clearer communication of safety plans to stakeholders and provides a realistic project experience via VR. This study marks an initial effort to leverage 8D BIM in construction projects, aiming to improve safety management by preemptively addressing potential accidents on-site.